Edgy Un/Intelligibilities: Feminist/Monster Theory Meets Ginger Snaps - Tapley, Heather (Atlantis, 2016)
This article analyzes the Canadian werewolf film Ginger Snaps (2000) through various feminist lenses at the intersection of sex, gender, and sexuality. While academic scholarship on the film at this particular intersection is extremely limited, articles that read Ginger Fitzgerald’s transformation into werewolf and menstruating female as empowering dominate the field. The following, however, moves to trouble such structural readings based in identity-politics and offers, in addition, a reading of political possibilities generated from poststructural approaches to monstrosity.